Stereo synthesiser fortunesrs & VCRs / Abd Rahim @ Hamdan Hj Hassan - Hassan, Abd Rahim @ Hamdan (1987)
Stereo reproduction relies on amplitiude and phase differences between two channel of a stereo system. To synthesise stereo from monophonic signals, therefore , we need to have some means of artificially recreayomh these amplitude and phase differences. In practice, this involve dividing the mono signal into several components than distributing these components between left and right channels.